Scientific and subject impact of Revista del Cuerpo Médico Hospital Nacional Almanzor Aguinaga Asenjo: An bibliometric analysis since 2011 to 2020 - Alhuay-Quispe, Joel (2022)
Introduction: Peru has several journals about biomedical areas, but a few serial publications are visible and indexing in different global indexing media. Objective: To analyze the main publication characteristics from Revista del Cuerpo Médico Hospital Nacional Almanzor Aguinaga Asenjo (Chiclayo) based on bibliometric methods. Methods: Descriptive study that analyzes 587 articles published by the journal from 2011 to 2020, based on bibliometric methods and indicators: citations, scientific impact and co-word analysis. Results: Original articles were the highest types of document published (60%; X̅=66). Published research articles on general medicine received more impact in previous years than the recents. Most frequent terms analyzed were studies about patients from hospitals in Chiclayo city (Lambayeque) with covid-19 clinical cases.  Conclusion: Revista del Cuerpo Médico HNAAA is emerging as an important scholarly publication to do visible local, national, and international production due to health subject coverage into medical specialties.